Gastrointestinal bleeding in hospitalized COVID‐19 patients: a propensity score matched cohort study. (29th January 2021) - Trindade, Arvind Julius; Izard, Stephanie; Coppa, Kevin; Hirsch, Jamie S.; Lee, Calvin; Satapathy, Sanjaya K.; ,
Abstract: Background and Aims: Gastrointestinal (GI) bleeding has been observed amongst patients hospitalized with COVID‐19. Recently, anticoagulation has shown to decrease mortality, but it is unclear whether this contributes to increased GI bleeding. The aims of this study are: (i) to examine whether there are risk factors for GI bleeding in COVID‐19 patients and (ii) to study whether there is a mortality difference between hospitalized patients with COVID‐19 with and without GI bleeding. Methods: This is a propensity score matched case–control study from a large health system in the New York metropolitan area between March 1st and April 27th. COVID‐19 patients with GI bleeding were matched 1:1 to COVID‐19 patients without bleeding using a propensity score that took into account comorbidities, demographics, GI bleeding risk factors and length of stay. Results: Of 11, 158 hospitalized with COVID‐19, 314 patients were identified with GI bleeding. The point prevalence of GI bleeding was 3%. There were no identifiable risk factors for GI bleeding. Use of anticoagulation medication or antiplatelet agents was not associated with increased risk of GI bleeding in COVID‐19 patients. For patients who developed a GI bleed during the hospitalization, there was an increased mortality risk in the GI bleeding group (OR 1.58, P  = 0.02). Conclusion: Use of anticoagulation or antiplatelet agents was not risk factors for GI bleeding in a large cohort of hospitalized COVID‐19 patients. Those with GI bleeding during the hospitalization had increased mortality. Abstract :